2020
DOI: 10.1097/jom.0000000000001864
|View full text |Cite
|
Sign up to set email alerts
|

Serum Metabolites in Hand-Arm Vibration Exposed Workers

Abstract: Objective: To investigate whether low molecular organic biomarkers could be identified in blood samples from vibration exposed workers using a metabolomics. Methods: The study population consisted of 38 metalworkers. All participants underwent a standardized medical examination. Blood samples were collected before and after work shift and analyzed with gas chromatography time-of-flight mass spectrometry. Multivariate modeling (orthogonal partial least-squares analysis with discriminant analysis [OPLS-DA]) were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…Recently, low molecular organic biomarkers were analysed in blood samples in vibration-exposed workers using metabolomics, showing differences in those with vibration-induced white fingers. 42 However, these metabolites were not possible to analyse in the present cohort. The interpretation of the present results is that vibration exposure is not sufficient to constantly increase any upregulation of a variety of biomarkers, except galanin, in the peripheral nerve that is mirrored in the plasma levels.…”
Section: Discussionmentioning
confidence: 77%
See 1 more Smart Citation
“…Recently, low molecular organic biomarkers were analysed in blood samples in vibration-exposed workers using metabolomics, showing differences in those with vibration-induced white fingers. 42 However, these metabolites were not possible to analyse in the present cohort. The interpretation of the present results is that vibration exposure is not sufficient to constantly increase any upregulation of a variety of biomarkers, except galanin, in the peripheral nerve that is mirrored in the plasma levels.…”
Section: Discussionmentioning
confidence: 77%
“…Thus, a number of potentially relevant biomarkers were selected and analysed, but were not found to be high in the plasma. Recently, low molecular organic biomarkers were analysed in blood samples in vibration-exposed workers using metabolomics, showing differences in those with vibration-induced white fingers 42. However, these metabolites were not possible to analyse in the present cohort.…”
Section: Discussionmentioning
confidence: 81%
“…Wahl et al 4 suggested that understanding the changes in the vasculature after vibration could shorten the latency period between symptom onset and definitive diagnosis. Vihlborg et al 5 used metabolomics analysis to observe different metabolites in vibration-exposed and nonexposed groups; some of these metabolites may be indicators of the health effects of vibration exposure. Furthermore, using an established rat vibration model, endothelin-1 (ET-1) was found to be aberrantly expressed in blood samples obtained from vibration-exposed rats 6 …”
mentioning
confidence: 99%